Identification of a putative transactivation domain in human Nanog - Oh, Jong-Hyun; Do, Hyun-Jin; Yang, Heung-Mo; Moon, Shin-Yong; Cha, Kwang-Yul; Chung, Hyung-Min; Kim, Jae-Hwan (Experimental & molecular medicine, 2005)
Nanog is a newly identified divergent homeodomain protein that directs the infinite propagation and sustains the pluripotency of embryonic stem cells. It has been reported that murine Nanog has two potent transactivation domains in N-terminal and C-terminal regions. Human Nanog (hNanog) polypeptide shares about 58% and 87% identity to the open reading frame and homeodomain of murine Nanog, respectively. However, the functional domains and molecular mechanisms of hNanog are poorly understood. In this study, for the first time, we presented that only C-terminus of hNanog contains a potent transactivation domain. Based on the amino acid sequences of homeobox domain, we roughly divided hNanog open reading frame into the three regions such as N-terminal, homeodomain and C-terminal regions and constructed either the fusion proteins between hNanog individual and Gal4 DNA binding domain or the context of native hNanog protein. Reporter assays by using reporter plamid containing Gal4 or Nanog binding site revealed that the only C-terminal region exhibited the significant fold induction of transactivation. However, interestingly, there was no significant activation through N-terminal region unlike murine Nanog, suggesting that C-terminal region may have more critical roles in the transcriptional activation of target genes. Taken together, the finding of a putative transactivation domain in hNanog may contribute to the further understanding of molecular mechanism on the regulation of downstream genes involved in self-renewal and pluripotency of human stem cells.